IL-17 Inhibition vs IL-23 Inhibition for Psoriatic Arthritis: An Ongoing Debate (Canadian Rheumatology Today, 2025)
The interleukin-17 (IL-17) and interleukin-23 (IL-23) pathways play a central role in the pathogenesis of psoriatic disease (PsD). This review outlines the immunobiology of these cytokine pathways and summarizes the current evidence on the efficacy and safety of IL-17 and IL-23 inhibitors across PsD domains, including peripheral arthritis, axial arthritis, enthesitis, dactylitis, psoriasis, and inflammatory bowel disease (IBD). IL-17 inhibitors, which target the effector cytokines IL-17A, IL-17F, or their receptors, have demonstrated robust efficacy in psoriasis, peripheral arthritis, and axial disease. IL-23 inhibitors act upstream by targeting the p19 subunit of IL-23 and show comparable efficacy in peripheral arthritis and psoriasis, though evidence for efficacy in axial disease remains limited. While IL-17 inhibitors carry a risk of IBD exacerbation, IL-23 inhibitors are considered therapeutic options for patients with coexisting IBD. In addition, radiographic progression appears better suppressed by IL-17 inhibitors, although emerging data suggest that IL-23 blockade may offer delayed benefits. Both IL-17 and IL-23 drug classes exhibit favourable safety profiles, with clinical trials suggesting slightly better tolerability for IL-23 inhibitors. Future directions include head-to-head comparisons, biomarker-guided treatment selection, and trials assessing long-term structural outcomes. Understanding the tissue- and cell-specific effects of inhibiting these cytokine pathways is key to optimizing therapy in PsD.